Pitfalls and clues in the prenatal diagnosis of abnormal origin of one of the pulmonary artery branches. (4th June 2018) - Quarello, Edwin; Paoli, Florent; Lafouge, Antoine; Stos, Bertrand; Gorincour, Guillaume
Abstract : What's already known about this topic? The abnormal origin of 1 of the pulmonary artery branches is a very rare malformative entity, for which prenatal ultrasonographic diagnosis remains difficult. What does this study add? We reviewed 3 cases, including 1 diagnosed after birth, for which we detailed the clues and pitfalls to reach (or miss) their identification. Knowledge of this malformation associated with a careful ultrasonographic strategy will allow early and optimal surgical management.